The Influence of the TGT (Teams Games Tournament) Type Cooperative Model on the Learning Motivation of Grade 2 Elementary School Students - Lilis Mustofiyah (Madrosatuna: Journal of Islamic Elementary School, 2018)
This study aims to determine the effect of the TGT type cooperative model (Teams Games Tournament) on student learning motivation. Researchers conducted research at SDN Cangkring Turi Prambon. The type of research used is a quantitative approach to experimental methods with Pre Experimental design. The type used is One Group Pretest-Posttest Design. The subjects taken were 21 grade II students at SDN Cangkring Turi Prambon. TGT learning model is used to find out the effect of the TGT learning model on the learning motivation of class II students of SDN Cangkring Turi Prambon. The results of this study indicate that the analysis of the data obtained is tcount of 20.80 and ttable of 1.725. Thus tcount > ttable, namely 20.80> 1.725, there is the effect of the TGT model on the learning motivation of class II students of SDN Cangkring Turi Prambon. While the results of the eta squared test obtained 0.955 ≥ 0.14 has the meaning of great influence.